A new gigantic species of Zeidora Adams, 1860 from Antarctic waters (Gastropoda: Fissurellidae) - Aldea, Cristian; Zelaya, Diego Gabriel; Troncoso, Jesús S.
A new species of Zeidora, Z. antarctica new species, is described from Bellingshausen Sea, Antarctica. The species is characterized by having a large and low shell, with delicate shell sculpture, spire extending beyond the shell’s outline, and relatively wide septum, curved at the anterior margin. Fil: Aldea, Cristian. Universidad de Vigo; España. Universidad de Magallanes; Chile Fil: Zelaya, Diego Gabriel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología Invertebrados; Argentina Fil: Troncoso, Jesús S. Universidad de Vigo. Facultad de Ciencias. Departamento de Ecología y Biología Animal; España